Evaluating a virtual reality dementia training experience using psychophysiological methods: A randomised controlled study - Stafford, Andrew; Bender, Stuart; Parsons, K.; Sung, Billy (2024)
Objectives: Virtual reality (VR) is increasingly used for training the dementia care workforce. It is unknown whether VR is superior to traditional training techniques in improving dementia care amongst practicing nurses. This study compared the impact of a VR application on nurses' knowledge and attitudes towards people living with dementia, to video-based, non-immersive training. Methods: Twenty-two registered and enrolled nurses were randomised to either interactive VR experience or video footage captured from within the app. Participants completed surveys pre- and post-training to assess their knowledge of dementia, attitudes towards dementia and person-centredness. Engagement with training was assessed objectively using facial electromyography, and subjectively with self-reported scales. Results: Virtual reality evoked objectively significant greater positive and negative emotional responses than video (positive emotion fEMG: VR mean.012 mV vs. video.005 mV, F[1, 20] = 8.70, p =.01; negative emotion fEMG: VR mean.018 mV vs. video.008 mV, F[1, 20] = 18.40, p <.001). Self-ratings of engagement and emotional state were similar. There was little change in the VR group's knowledge of, and attitudes towards, dementia; the video group's dementia knowledge improved (total DKAS mean differences: VR.1 t =.07, df = 9, p =.95 vs. video −2.3 t = −2.265, df = 11, p =.045). Conclusions: Virtual reality is more engaging than traditional training in highly experienced dementia care practitioners. Despite this, VR may not be superior to traditional training techniques to improve knowledge and attitude for many learners. A focus of future research in the area should be on how to capitalise on VR's greater emotional engagement so that Australia's nursing workforce is better equipped to care for the increasing number of people living with dementia.